Hydrogen production by the water-gas shift reaction using CuNi/Fe2O3 catalyst - Jha, Ajay; Jeong, Dae-Woon; Shim, Jae-Oh; Jang, Won-Jun; Lee, Yeol-Lim; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Science & Technology, 2015)
Incorporation of both Cu and Ni together into the crystalline lattice of Fe2O3 results in a significant increase in the catalytic activity and also suppresses the methanation reaction in the high-temperature water-gas shift (HT-WGS) reaction. CuNi/Fe2O3 exhibited the highest CO conversion with negligible CH4 selectivity at the extremely high GHSV of 101 000 h(-1) (X-CO = 85% at 400 degrees C). The high activity of CuNi/Fe2O3 catalyst is mainly due to the increase in the lattice strain and the decrease in the binding energy of lattice oxygen. In addition, X-ray photoelectron spectroscopy (XPS) results provide direct evidence for the formation of surface CuNi alloy, which plays a critical role in suppressing the methanation reaction. The detailed characterization by powder X-ray diffraction (XRD), XPS, BET, and H-2 temperature-programmed reduction (TPR) techniques was used to understand the role of dopants on host iron oxides in the enhancement of catalytic activity for HT-WGS reaction.

Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

Effect of alkali and alkaline earth metal on Co/CeO2 catalyst for the water gas shift reaction of waste derived synthesis gas - Lee, Yeol-Lim; Jha, Ajay; Jang, Won-Jun; Shim, Jae-Oh; Rode, Chandrashekhar V.; Jeon, Byong-Hun; Bae, Jong Wook; Roh, Hyun-Seog (Applied Catalysis A-General, 2018)
We prepared a series of alkali (Na and K) and alkaline earth metal (Ca and Ba) promoted Co/CeO2 catalysts to investigate the effect of the promoter on the catalytic performance of the catalyst in the high-temperature water gas shift (WGS) reaction of waste derived synthesis gas. Interestingly, alkali metal promoted catalysts deactivated rapidly compared to alkaline earth metal promoted catalysts. Alkaline earth metal promoted catalysts showed relatively higher stability (>50 h) even at a very high gas hourly space velocity of 143,000 h(-1). X-ray diffraction (XRD) and transmission electron microscopy (TEM) results reveal that the higher stability of the alkaline earth metal promoted catalysts was due to the strong resistance to sintering, showing a relatively small crystallite size of metallic cobalt compared to the alkali metal promoted catalysts after WGS reaction.
Keywords: Alkaline earth metal; Co/CeO2; High temperature water-gas shift; Sintering resistance; stability; Waste derived synthesis gas

Effect of titration time on the catalytic performance of Cu/CeO2 catalysts for water-gas shift reaction - Na, Hyun-Suk; Shim, Jae-Oh; Jang, Won-Jun; Jeon, Kyung-Won; Kim, Hak-Min; Lee, Yeol-Lim; Lee, Da-We; Yoo, Seong-Yeun; Bae, Jong Wook; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Today, 2018)
We herein report the preparation of ceria (CeO2) via a simple precipitation method for use as a catalyst support in the water-gas shift (WGS) reaction. More specifically, we optimized the titration time required to obtain highly active CeO2-supported catalysts for the WGS reaction. As such, Cu was employed as the active metal coupled with the CeO2 support. Notably, the CeO2-0 supported Cu catalyst (where the precipitant was immediately injected into a cerium nitrate solution) exhibited the highest CO conversion at a gas hourly space velocity of 36,050 h(-1). This high catalytic activity of the Cu/CeO2-0 catalyst was mainly due to its high Brunauer-Emmett-Teller (BET) surface area, enhanced Cu dispersion, high number of oxygen vacancies, and enhanced reducibility.